Makna Simbolik dalam Tradisi Appassili Bunting Adat Makassar di Desa Banggae Kabupaten Takalar: Tinjauan Semiotika Pierce - Rindiani, Rindiani; Hajrah, Hajrah; Fitri, Sakinah (Fakultas Bahasa dan Sastra Indoensia, 2024)
This research aims to describe icons, indices and symbols found in the process of implementing appassili bunting in Banggae village, Regency Takalar is viewed from Charles Sanders Peirce's semiotic theory. This type of research is qualitative with a qualitative descriptive research design. The method used in collecting data for this research are observation, interviews, and documentation. The results of this research show that in the process of implementing tradition Appassili bunting in Banggae village, Takalar Regency has the meaning of (1) icon namely tai bani and doek rancing (2) the meaning of the index is incense, akganrag, and akjeknek ri timunganga. (3) the meaning of the symbol, namely jakjakkang, kaluku na golla eja, tai bani, doek ri jakjakkang, roar lekok, lekok sirikaya, thief's curve, passili's curve, campaga's curve, scrambled, book's curve, rappo, jeknek passili, katoang, pammajak, cingcing bulaeng, kanrejawa attitudeparak. In general, the meaning contained in the appassili procession tradition pregnancy in Banggae village, Takalar Regency is to be avoided ugliness before approaching the contract, obtaining abundant fortune, and prosperous home life